Heavy-mineral analysis in Polish investigations of Quaternary deposits: a review - Marcinkowski, Bogusław; Mycielska-Dowgiałło, Elżbieta (Geologos, 2013)
The composition of heavy-mineral assemblages is one of the main textural features of sediments because they can have significant value for the interpretation of, among others, their depositional environment, their depositional processes, and their stratigraphic position. Distinctive features of heavy minerals include their resistance to chemical weathering and mechanical abrasion, their habit, and their density. These parameters are the most widely used in the heavy-mineral research of Quaternary deposits in Poland, as well as in such research in other countries conducted by Polish scientists. Several other heavy-mineral parameters can also be used in various types of interpretation. It is discussed whether heavy-mineral analysis is decisive in the evaluation of deposits or whether it plays mainly a role that may support evidence obtained by other types of analysis. The attention is mainly devoted to transparent heavy minerals; the significance of opaque heavy minerals for interpretational purposes is only mentioned.